2012
DOI: 10.1021/nn204657n
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Investigation of Nanoparticle Interaction with a Model Pulmonary Surfactant Monolayer

Abstract: The pulmonary surfactant film spanning the inner alveolar surface prevents alveolar collapse during the end-exhalation and reduces the work of breathing. Nanoparticles (NPs) present in the atmosphere or nanocarriers targeted through the pulmonary route for medical purposes challenge this biological barrier. During interaction with or passage of NPs through the alveolar surfactant, the biophysical functioning of the film may be altered. However, experimental evidence showing detailed biophysical interaction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 48 publications
5
75
0
Order By: Relevance
“…It was found that the hydrophobic NPs immerse themselves in the hydrophobic tails of the interfacial DPPC molecules, while hydrophilic NPs adsorb onto the hydrophilic head-groups of the interfacial DPPC molecules. This finding is in good agreement with previous in-vitro , in-vivo and in-silico translocation results [39,46,5458]. …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It was found that the hydrophobic NPs immerse themselves in the hydrophobic tails of the interfacial DPPC molecules, while hydrophilic NPs adsorb onto the hydrophilic head-groups of the interfacial DPPC molecules. This finding is in good agreement with previous in-vitro , in-vivo and in-silico translocation results [39,46,5458]. …”
Section: Discussionsupporting
confidence: 93%
“…Both in-vitro experiments [3539] and computer simulations [4046] have confirmed that the phospholipids of PS undergo surface phase transition during the compression-expansion cycles. During film compression, phospholipid monolayers undergo surface phase transitions from a “fluid-like” LE phase to a “solid-like” LC phase, which is opposite to the direction of phase transition during film expansion.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…These results are in good agreement with previous in vitro and in silico studies that show hydrophobic NP adsorb to the surfactant film where the nano-bio interactions govern the surfactant inhibition. 11,12,14,20 …”
Section: Resultsmentioning
confidence: 99%
“…Hydrophobic polyorganosiloxane nanoparticles do not substantially affect the structural organization of a model pulmonary surfactant film at low concentrations (e.g., 10 μg/mL) but significantly affect such properties at high concentrations (e.g., 3000 μg/mL). 82 Polystyrene nanoparticles with a diameter of 20 nm demonstrate greater interactions with the endothelial model membrane than those with a diameter of > 60 nm. 64 Perturbations from nanoparticles may cause pore formation in lipid bilayers.…”
Section: Nanoparticle-biomolecule Interactionsmentioning
confidence: 95%